2016
DOI: 10.1007/s11356-016-7276-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable packaging materials conception based on starch and polylactic acid (PLA) reinforced with cellulose

Abstract: The plastic materials used for packaging are increasing leading to a considerable amount of undegradable solid wastes. This work deals with the reduction of conventional plastics waste and the natural resources preservation by using cellulosic polymers from renewable resources (alfa and luffa). Plasticized starch films syntheses were achieved at a laboratory scale. These natural films showed some very attractive mechanical properties at relatively low plasticizers levels (12 to 17 % by weight). Furthermore, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 44 publications
0
27
0
3
Order By: Relevance
“…together with a cost competitive price and easy processing by conventional techniques. For these reasons, PLA finds increasing uses in a wide range of industrial sectors such as automotive [ 1 , 2 , 3 , 4 ], medical devices [ 5 , 6 ], construction and building, 3D printing [ 7 , 8 ], packaging [ 9 , 10 , 11 , 12 ], wood plastic composites (WPCs) [ 13 , 14 ], and so on. Nevertheless, PLA is a very fragile polymer with very low toughness.…”
Section: Introductionmentioning
confidence: 99%
“…together with a cost competitive price and easy processing by conventional techniques. For these reasons, PLA finds increasing uses in a wide range of industrial sectors such as automotive [ 1 , 2 , 3 , 4 ], medical devices [ 5 , 6 ], construction and building, 3D printing [ 7 , 8 ], packaging [ 9 , 10 , 11 , 12 ], wood plastic composites (WPCs) [ 13 , 14 ], and so on. Nevertheless, PLA is a very fragile polymer with very low toughness.…”
Section: Introductionmentioning
confidence: 99%
“…According to Masmoudi et al ., the use of starch or thermoplastic starch (TPS) as a filler may cheapen the obtained polymeric material and emphasize its rapid degradation and hydrolysis. However, it has been observed that its addition compromises the mechanical properties of composites.…”
Section: Introductionmentioning
confidence: 99%
“…7 In this regard, scientists have focused on using biodegradable polymers such as poly(lactic acid) (PLA) and starch. 8,9 Regardless of their environmental friendliness, they are not widely utilized in packaging industry due to their low mechanical properties, processability, barrier properties, and high cost. 10,11 Bao et al investigated gas barrier properties of PLA films using the time-lag method.…”
Section: Introductionmentioning
confidence: 99%